Pregunta
upstudy study bank question image url

(d) Determine (by showing all the steps) the equilibrium point(s) of the below differential equation, by strictly using an analytical approach (4 marks penalty if inspection is used). \[ \frac{d y}{d t}=-65-2\left(\sqrt{y^{3}-1}\right)^{-1}+3\left(\sqrt{y^{3}-1}\right)^{-1} \]

Ask by Jimenez Pope. in South Africa
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

The equilibrium point is \( y = \sqrt[3]{\frac{4226}{4225}} \).

Solución

To determine the equilibrium point(s) of the differential equation \[ \frac{dy}{dt} = -65 - 2\left(\sqrt{y^{3}-1}\right)^{-1} + 3\left(\sqrt{y^{3}-1}\right)^{-1}, \] we need to find the value(s) of \( y \) where \( \frac{dy}{dt} = 0 \). ### Step 1: Set the Differential Equation to Zero Set \( \frac{dy}{dt} = 0 \): \[ 0 = -65 - 2\left(\sqrt{y^{3}-1}\right)^{-1} + 3\left(\sqrt{y^{3}-1}\right)^{-1} \] ### Step 2: Simplify the Equation Combine the terms involving \( \left(\sqrt{y^{3}-1}\right)^{-1} \): \[ 0 = -65 + \left(-2 + 3\right)\left(\sqrt{y^{3}-1}\right)^{-1} \] \[ 0 = -65 + \left(1\right)\left(\sqrt{y^{3}-1}\right)^{-1} \] \[ 65 = \left(\sqrt{y^{3}-1}\right)^{-1} \] ### Step 3: Solve for \( \sqrt{y^{3}-1} \) Take the reciprocal of both sides: \[ \sqrt{y^{3}-1} = \frac{1}{65} \] ### Step 4: Square Both Sides Square both sides to eliminate the square root: \[ y^{3} - 1 = \left(\frac{1}{65}\right)^{2} \] \[ y^{3} - 1 = \frac{1}{4225} \] ### Step 5: Solve for \( y^{3} \) \[ y^{3} = 1 + \frac{1}{4225} \] \[ y^{3} = \frac{4225}{4225} + \frac{1}{4225} = \frac{4226}{4225} \] ### Step 6: Take the Cube Root \[ y = \sqrt[3]{\frac{4226}{4225}} \] ### Conclusion The equilibrium point is: \[ y = \sqrt[3]{\frac{4226}{4225}} \] **Final Answer:** After simplifying, the sole equilibrium is the real root of y³ = 4226⁄4225. Thus, y = ∛(4226 ⁄ 4225)

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To find the equilibrium point(s) of the given differential equation \[ \frac{d y}{d t} = -65 - 2\left(\sqrt{y^{3}-1}\right)^{-1} + 3\left(\sqrt{y^{3}-1}\right)^{-1}, \] we start by setting the right-hand side equal to zero: \[ 0 = -65 - 2\left(\sqrt{y^{3}-1}\right)^{-1} + 3\left(\sqrt{y^{3}-1}\right)^{-1}. \] This simplifies to: \[ 0 = -65 + \left(\sqrt{y^{3}-1}\right)^{-1}. \] Rearranging gives us: \[ \left(\sqrt{y^{3}-1}\right)^{-1} = 65. \] Taking the reciprocal, we obtain: \[ \sqrt{y^{3}-1} = \frac{1}{65}. \] Next, we square both sides: \[ y^{3} - 1 = \left(\frac{1}{65}\right)^{2}. \] Calculating \(\left(\frac{1}{65}\right)^{2}\): \[ y^{3} - 1 = \frac{1}{4225}. \] Adding 1 to both sides provides: \[ y^{3} = 1 + \frac{1}{4225} = \frac{4225 + 1}{4225} = \frac{4226}{4225}. \] Taking the cube root of both sides gives us the equilibrium point: \[ y = \sqrt[3]{\frac{4226}{4225}}. \] This is the analytical process to find the equilibrium point(s).

preguntas relacionadas

Latest Calculus Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad